Chronic unpredictable mild stress alters odor hedonics and adult olfactory neurogenesis in mice - Athanassi, Anna; Breton, Marine; Chalençon, Laura; Brunelin, Jérome; Didier, Anne; Bath, Kevin; Mandairon, Nathalie (Frontiers in Neuroscience, 2023)
Experiencing chronic stress significantly increases the risk for depression. Depression is a complex disorder with varied symptoms across patients. However, feeling of sadness and decreased motivation, and diminished feeling of pleasure (anhedonia) appear to be core to most depressive pathology. Odorants are potent signals that serve a critical role in social interactions, avoiding danger, and consummatory behaviors. Diminished quality of olfactory function is associated with negative effects on quality of life leading to and aggravating the symptoms of depression. Odor hedonic value (I like or I dislike this smell) is dominant feature of olfaction and guides approach or avoidance behavior of the odor source. The neural representation of the hedonic value of odorants is carried by the granule cells in the olfactory bulb, which functions to modulate the cortical relay of olfactory information. The granule cells of the olfactory bulb and those of the dentate gyrus are the two major populations of cells in the adult brain with continued neurogenesis into adulthood. In hippocampus, decreased neurogenesis has been linked to development or maintenance of depression symptoms. Here, we hypothesize that chronic mild stress can alter olfactory hedonics through effects on olfactory bulb neurogenesis, contributing to the broader anhedonia phenotype in stress-associated depression. To test this, mice were subjected to chronic unpredictable mild stress and then tested on measures of depressive-like behaviors, odor hedonics, and measures of olfactory neurogenesis. Chronic unpredictable mild stress led to a selective effect on odor hedonics, diminishing attraction to pleasant but not unpleasant odorants, an effect that was accompanied by a specific decrease in adult neurogenesis and of the percentage of adult-born cells responding to pleasant odorants in the olfactory bulb.